Digging the topology of rock art in northwestern Patagonia. (9th September 2019) - Vargas, Fernando E; Lanata, José L; Abramson, Guillermo; Kuperman, Marcelo N; Fiore, Danae
Abstract: We present a study on the rock art of northern Patagonia based on network analysis and communities detection. We unveil a significant aggregation of archaeological sites, linked by common rock art motifs that turn out to be consistent with their geographical distribution and archaeological background of hunter-gatherer stages of regional peopling and land use. This exploratory study will allow us to approach more accurately some social strategies of visual communication entailed by rock art motif distribution, in space and time.